Musalogue: a catalogue of Musa germplasm: Papua New Guinea collecting missions 1988-89 - Arnaud, Elizabeth; Horry, J.P.; International Network for the Improvement of Banana and Plantain (1997)
This issue of Musalogue is intended to facilitate and encourage the utilisation of the germplasm collected in Papua New Guinea. The collecting of Papua New Guinea's unique diploid genepool, for preservation as well as for use in breeding programmes, was recommended during an international workshop on banana and plantain breeding strategies organised by ACIAR and INIBAP in 1986. Collecting missions took place in 1988 and 1989 and the collected germsplam was sent to QDPI for virus indexing and evaluation. During 1993-94, 242 of the accessions collected in Papua New Guinea were evaluated at the QDPI South Johnstone Research Station, within the INIBAP project ”Taxonomic Characterization of the Papua New Guinea Banana Germplasm Collection”. This first issue of Musalogue provides information on the accessions relating to their phenotypic characteristics, agronomic performance and reaction to yellow Sigatoka disease. Observations recorded at the collecting sites by the collectors are also included. Although a number of accessions have been classified using molecular markers by CIRAD, France, classifications are generally based on morphological characteristics and in all cases, should be considered tentative.